In vitro cytotoxicity assessment of ruxolitinib on oligodendrocyte precursor cell and neural stem/progenitor cell populations - Lim, Cheng-Wei; Hamanaka, Gen; Liang, Anna C.; Chan, Su Jing; Ling, King-Hwa; Lo, Eng H.; Arai, Ken; Cheah, Pike See
JAK-STAT signaling cascade has emerged as an ideal target for the treatment of myeloproliferative diseases, autoimmune diseases, and neurological disorders. Ruxolitinib (Rux), is an orally bioavailable, potent and selective Janus-associated kinase (JAK) inhibitor, proven to be effective to target activated JAK-STAT pathway in the diseases previously described. Unfortunately, limited studies have investigated the potential cytotoxic profile of Rux on other cell populations within the heterogenous CNS microenvironment. Two stem and progenitor cell populations, namely the oligodendrocyte precursor cells (OPCs) and neural stem/progenitor cells (NSPCs), are important for long-term maintenance and post-injury recovery response of the CNS. In light of the limited evidence, this study sought to investigate further the effect of Rux on proliferating and differentiating OPCs and NSPCs populations. In the present study, cultured rat OPCs and NSPCs were treated with various concentrations of Rux, ranging from 2 μM to 20 μM. The effect of Rux on proliferating OPCs (PDGF-R-α+) and proliferating NSPCs (nestin+) was assessed via a 3-day Rux treatment, whereas its effect on differentiating OPCs (MBP+/PDGFR- α+) and differentiating NSPCs (neurofilament+) was assessed after a 7-day treatment. Cytotoxicity of Rux was also assessed on OPC populations by examining its influence on cell death and DNA synthesis via YO-PRO-1/PI dual-staining and BrdU assay, respectively. The results suggest that Rux at a dosage above 10 μM reduces the number proliferating OPCs, likely via the induction of apoptosis. On the other hand, Rux treatment from 2.5 μM to 20 μM significantly reduces the number of differentiating OPCs by inducing necrosis. Meanwhile, Rux treatment has no observable untoward impact on NSPC cultures within the dosage range tested. Taken together, OPCs appears to be more vulnerable to the dosage effect of Rux, whereas NSPCs are not significantly impacted by Rux, suggesting a differential mechanism of actions of Rux on the cell types.